Photophysical and electrochemical properties of novel pyridyl-ethylene Re-complexes - Machado, Rubén; Vargas, Franklin; Arce, Alejandro; Rivillo, David; De Sanctis, Ysaura; Jorge, Gilberto; Martinez, José; D”™OrnelasLindora (Ciencia)
The absorption and fluorescence spectra at different excitation wavelengths of the recently reported rhenium carbonyl complexes [Re2(µ:ï¨3-C12H10N2)(CO)8 (1), [Re2(µ-H)(µ:ï¨3-C12H9N2)(CO)7 (2) and [Re2(µ-H)(µ:ï¨5-C12H9N2)(CO)6 (3) have been studied and compared between them with the aim to evaluate their potential as molecular switches and charge transfer species. Their photostability in dichloromethane solutions (aerobic conditions) under UV-A and UV-B light irradiation, and photoinduced charge transfer reactions with tetrazolium blue were analyzed. The redox properties of complexes 1-3 have been examined by cyclic voltammetry: the behavior of complexes 1 and 3 is very similar, giving quasi-reversible oxidation-reduction processes, while for 2 a totally irreversible oxidation-reduction process was observed.